Basal Energy Expenditure (BEE) in Pencak Silat Athletes - Rahman, Holirul; Jalil, Rasyidah; Ulpi, Wahyuni (Department of Physical Education, Sport, Health and Recreation, 2022)
The martial art of pencak silat as a method of fighting philosophically teaches spiritual and physical education to help its devotees live the noble moral values ​​in it. The material object of this research is pencak silat and the formal object is the art philosophy or aesthetics of the pencak silat. This study aims to describe the Basal Energy Expenditure (BEE) seen from the status of .The research method used is descriptive research method with a quantitative approach. As for the research subjects, namely the pencak silat athletes in the city of Palopo and Luwu Regency, the sample size is 27 people with saturated sampling technique, using data analysis techniquesThis means a technique for a study whose data can be measured by scoring or numerically. The data obtained were processed through statistical and computerized methods. From the results of the study above, BEE 1501 was thin, the frequency was 1 and the percentage was 3.7%. Normal BEE 1268-1773, frequency 21 and percentage 77.8%. Overweight BEE 1415-1842, frequency 3 and percentage 11.1%. Obesity BEE 1924-1948 frequency 2 and percentage 7.4% . The test results showed that the average body weight of the sample of pencak silat athletes that I studied had normal BEE.